1997
DOI: 10.1159/000237447
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Circulating lnterleukin-4 and lnterleukin-10 in Kawasaki Disease

Abstract: For analysis of the cytokine network in Kawasaki disease (KD), we measured over time the plasma levels of interferon (IFN)-γ interleukin (IL)-4 and IL-10 in patients with KD. Fifteen patients with KD were studied. Eight healthy children were selected as control subjects. Circulating IFN-γ levels were measured by immunoradiometric assay, and IL-4 and IL-10 levels were measured by enzyme-linked immunosorbent assay. The results were as follows: (1) The plasma levels of IFN-γ in KD patients in the acute phase were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 9 publications
4
56
2
1
Order By: Relevance
“…Previous studies have reported that patients with Kawasaki disease exhibit significantly higher serum levels of IL-4 and IFN-γ, Th 1 and Th 2 cytokines. These levels decrease in the recovery period, possibly resulting from activated Th 1 and Th 2 (16,17). Similarly, we found that serum IL-4 and IFN-γ levels in a mouse model of Kawasaki disease are significantly higher compared to those of healthy mice.…”
supporting
confidence: 71%
“…Previous studies have reported that patients with Kawasaki disease exhibit significantly higher serum levels of IL-4 and IFN-γ, Th 1 and Th 2 cytokines. These levels decrease in the recovery period, possibly resulting from activated Th 1 and Th 2 (16,17). Similarly, we found that serum IL-4 and IFN-γ levels in a mouse model of Kawasaki disease are significantly higher compared to those of healthy mice.…”
supporting
confidence: 71%
“…Recent evidence [61][62][63] suggests an important role for IL-10, but not for IL-4 in the Th2 response. However, as has been proposed by others, [64][65][66][67] we analyzed IL-4 and IFN-␥ as indicators of Th2 and Th1, respectively. These subpopulations may in part explain the behavior observed in the cohorts of patients with invasive amoebiasis and asymptomatic carriers, considered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Specific IgE to Japanese cedar pollens was measured by the CAP system [11]. IL-4 was measured with our chemiluminescent enzyme-linked immunosorbent assay (ELISA) [12], and the justification of the method employed in this study has been described elsewhere [12,13]. In brief, microtitre plates were coated with mouse monoclonal antihuman IL-4 antibody (R & D Systems, Minneapolis, MN, USA) and after incubation with serum samples or purified recombinant IL-4 (R & D System, Minneapolis, MN, USA) plates were developed with biotinylated mouse anti-human IL-4 antibody (Pharmingen, San Diego, CA, USA) followed by avidine-alkaline phosphatase conjugate (Tago, Camarillo, CA, USA).…”
Section: Methodsmentioning
confidence: 99%